PELAKSANAAN PENILAIAN RANAH KETERAMPILAN BERDASARKAN KURIKULUM 2013 PADA MATA PELAJARAN IPS SMP - M. Khoirul Annas Waladul Mufid (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2020)
Changes to the assessment in K13 give problems to teachers in implementing them according to the guidelines. This research focuses on discussing the process of implementing the skills assessment by social studies teachers and the obstacles they face. A descriptive qualitative approach with the narrative design was used to discuss the focus of this research. Data collection techniques with observation, interviews, and documentation of social science subject teachers in Malang. Data were analyzed using an interactive data analysis model, consisting of (1) collection, (2) presentation, (3) reduction, and (4) verification. The results show that the implementation of the skills assessment is appropriate with the guidelines. However, there are some obstacles, teacher confusion in determining activities, students who are not active and varied, time, and teachers who do not have the heart to give values ​​objectively. Therefore, it is necessary to increase teacher's competence, one of them is structured guidance.